Secondary Cases of Delta Variant Coronavirus Disease 2019 Among Vaccinated Healthcare Workers With Breakthrough Infections is Rare. (25th October 2021) - Waldman, Sarah E; Buehring, Tara; Escobar, Daniel J; Gohil, Shruti K; Gonzales, Ralph; Huang, Susan S; Olenslager, Keith; Prabaker, Kavitha K; Sandoval, Tessa; Yim, Jennifer; Yokoe, Deborah S; Cohen, Stuart H
Abstract: In a retrospective, cohort study at 4 medical centers with high coronavirus disease 2019 vaccination rates, we evaluated breakthrough severe acute respiratory syndrome coronavirus 2 Delta variant infections in vaccinated healthcare workers. Few work-related secondary cases were identified. Breakthrough cases were largely due to unmasked social activities outside of work.